In silico identification and in Vitro assessment of a potential anticancer peptide sequence retrieved from the red sea metagenomics library - Imam, Mona Elradi (AUC Knowledge Fountain, 2016)
Cancer is imposing a worldwide health concern with alarming morbidity and mortality rates. Its burden stems from its increasing incidence along with depletion of efficient therapeutic options. Current conventional anticancer therapies; surgery, radiotherapy and chemotherapy are barely effective with deleterious side effects that ruin patients' quality of life. There is a paradigm shift in the interest of pharmaceutical industry towards a new class of peptide based drugs offering more selectivity, easier synthesis, wider safety profile and lower cost of manufacture. Anticancer peptides (ACPs) have gained interest in the last few decades due to their intrinsic properties such as cationicity and small size enabling them to be selective and effective anticancer agents. In our study, we made use of the publicly available databases of ACPs and the Red Sea metagenomics data, generated during AUC/KAUST Red Sea microbiome project. Our experimental design consists of two phases; in silico analysis followed by in vitro validation of the computational results. In silico analysis resulted in a set of peptide hits from our library that share similar composition to ACPs. One hit was submitted for further in silico prediction of structure and function. The sequence was then chemically synthesized for subsequent in vitro functional assessment through cytotoxicity assay (MTT assay), apoptosis/necrosis detection assay (Annexin/PI assay) and RNA expression analysis of Caspase 3.The cancer cell lines used were U2OS, HepG2, MCF7 and HeLa. The peptide showed evident, yet variable, dose dependent cytotoxicity in all tested cell lines. Membranolysis and Apoptosis could be concluded as possible mechanisms of action from the results of annexin assay and RT-PCR that showed overexpression of Caspase 3 in peptide treated U2OS cells. Our results, despite being consistent and in line with each other, more investigative techniques should be done for confirmation and elucidation of the molecular mechanism of action of our peptide lead.